Clinical Features in Metastatic Bone Disease with and without Pathological Fractures: A Comparative Study - Putu Garry; Mouli Edward; Rosy Setiawati; Sjahjenny Mustokoweni; Ferdiansyah Mahyudin (Humanistic Network for Science and Technology (HNST), 2019)
Background: Pathological fracture complications such as impaired clinical features is suspected to increase the mortality in MBD. In Indonesia, the habit of delayed seeking of medical treatment was common and potentially led to pathological fracture. Aim: This study compared the clinical features between MBD with and without pathological fracture. Methods: This was a retrospective study of MBD at Dr. Soetomo General Hospital in 2011-2015. We compared the clinical features by pain in Visual Analog Scale (VAS); general health presentation represented by laboratory findings; and the history of non-medical treatments. Results: 64 patients had MBD were included in this study. 37 (57.8%) of them presented with pathological fractures, and 27 (42.2%) without. Pain was the most common chief complaint (76.5%). No significant difference found between the MBD with and without pathological fracture in all variables (p=0.122; p=0.64; p=0.823; p=0.417, p=1.000 for VAS, hemoglobin, albumin, calcium, and history of non-medical treatment respectively). This probably associated with the therapy and a variety of primary tumors underlying the MBD. However, 6 out of 10 patients with history non-medical treatment presented with fractures. Conclusion: There's no significant difference in clinical features of MBD from both groups, while those with fractures had worse conditions. Keywords: Metastatic bone disease, Pathological fracture, Clinical features